Eksplorasi Cendawan Endofit Asal Padi Sawah sebagai Agens Pengendali Penyakit Blas pada Padi Sawah - Irwanto Sucipto; Abdul Munif; Yadi Suryadi; Efi Toding Tondok (Jurnal Fitopatologi Indonesia, 2015)
Blast disease (Pyricularia oryzae) in Indonesia is initially known to cause problem on upland rice, but since 2000’s blast disease was also reported occurred on lowland rice. Application of endophytic fungi is very potential to be used as disease control method. This study was conducted to isolates endophytic fungi from lowland rice, and determine its capability to reduce  blast disease severity. Isolation of endophytic fungi was done from root, tiller, and the leaves of lowland rice.  Kencana Bali variety was used for in vivo inhibition test due to its most susceptible response against P. oryzae. Forty seven endophytic fungi isolates were obtained from Bogor, Sukabumi and Blitar. Based on colony morphology, endophytic fungi can be differentiated into 9 morphotype. Four out of fourteen endophytic fungi showed antibiosis activity in in vitro inhibition test against P. oryzae. Inhibition test conducted on Kencana Bali variety in the green house showed that four isolates was able to suppress blast disease development by 30-70%.